Machado de Assis, tradutor de Hugo - Flores, Diego do Nascimento Rodrigues (2007)
The Machado de Assis who is the object of this dissertation, the translator Machado de Assis, shall be examined here with the purpose of taking further steps towards a profile of his character as a translator. Thus, it was assigned to this stage of the research to examine the only novel translated integrally by the nineteenth century writer, Les travailleurs de la mer, by Victor Hugo. Firstly, we visited authors who theorize translation aiming at finding the arguments which would establish the ground for the form which this study would assume. We adopted as our fundamental theoretical reference the work of Antoine Berman, whose proposal for translation criticism is analyzed in one of the chapters in this work, and from which we outlined the method that should be used in the study of Machado’s translation. The next step was to try to delineate a profile of the translator basing ourselves in studies which preceded ours, as well as in texts by Machado himself. We did so with the objective of studying his translation taking into consideration the data we could gather about Machado’s relation with translation practice. However, before putting original and translation side by side, we dedicated a whole chapter to the analysis of the novel in question, which helped us determine which excerpts of the work would be elected for further analysis, accomplished later on. We henceforth arrive at the critical study of Machado’s translation, also taking into account two other translations of the same novel, aiming at comparing Machado’s decisions with those of other translators. What we looked for when comparing original and translation were not the “wrong” or “right” choices of the translator, but tried to evaluate his decisions bearing in mind that which the original proposed, even when the translator clearly shifted his course from what Hugo had written. When observing the young Machado de Assis in action, we noticed that even facing numberless adversities, the translator not only performed a memorable task, as well as proved to be a professional both competent and conscious, who does not exempt himself from the changes he believed to be necessary, even though that meant leaving the original author aside and that, moreover, there seemed to be a growing tuning in between author and translator during the translation process.